Legal Protection of Good Faith Buyers in Resolution of Land Rights Disputes - Rafael Tunggu (Green Publisher Indonesia, 2024)
This research was carried out to determine and analyze legal protection for buyers in good faith in resolving land rights disputes. To achieve the research objectives, a document study has been carried out on the Decision of the Makassar District Court Number: 318/Pdt.G/BTH/2014, with three approaches, namely the conceptual approach, legislation and legal objectives. The research results show that in his legal considerations the judge stated that if the land sale and purchase transaction does not fulfill the